1997
DOI: 10.1084/jem.186.1.47
|View full text |Cite
|
Sign up to set email alerts
|

4-1BB Costimulatory Signals Preferentially Induce CD8+ T Cell Proliferation and Lead to the Amplification In Vivo of Cytotoxic T Cell Responses

Abstract: The 4-1BB receptor is an inducible type I membrane protein and member of the tumor necrosis factor receptor (TNFR) superfamily that is rapidly expressed on the surface of CD4+ and CD8+ T cells after antigen- or mitogen-induced activation. Cross-linking of 4-1BB and the T cell receptor (TCR) on activated T cells has been shown to deliver a costimulatory signal to T cells. Here, we expand upon previously published studies by demonstrating that CD8+ T cells when compared with CD4+ T cells are preferentially respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

38
600
4
7

Year Published

1998
1998
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 712 publications
(654 citation statements)
references
References 11 publications
38
600
4
7
Order By: Relevance
“…4-1BB (CD137) is a receptor belonging to the tumor necrosis factor receptor (TNFR) superfamily (Goodwin et al, 1993;Kwon et al, 1987;Lotz et al, 1996;Setareh et al, 1995) which is expressed in an activation-dependent manner on T cells Pollok et al, 1993;Schwarz et al, 1996;Shuford et al, 1997) and constitutively on CD4 + CD25 + regulatory T cells (McHugh et al, 2002). Although 4-1BB is mainly involved in regulating activated T lymphocyte functions, expression of 4-1BB has been noted on non-T cells such as B cells, monocytes, macrophages, dendritic cells, eosinophils, and neutrophils (Futagawa et al, 2002;Heinisch et al, 2000;Schwarz et al, 1995;Watts et al, 2005;Wilcox et al, 2002;Yoon et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…4-1BB (CD137) is a receptor belonging to the tumor necrosis factor receptor (TNFR) superfamily (Goodwin et al, 1993;Kwon et al, 1987;Lotz et al, 1996;Setareh et al, 1995) which is expressed in an activation-dependent manner on T cells Pollok et al, 1993;Schwarz et al, 1996;Shuford et al, 1997) and constitutively on CD4 + CD25 + regulatory T cells (McHugh et al, 2002). Although 4-1BB is mainly involved in regulating activated T lymphocyte functions, expression of 4-1BB has been noted on non-T cells such as B cells, monocytes, macrophages, dendritic cells, eosinophils, and neutrophils (Futagawa et al, 2002;Heinisch et al, 2000;Schwarz et al, 1995;Watts et al, 2005;Wilcox et al, 2002;Yoon et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Extensive evidence supports the role of 4-1BB as a costimulatory molecule that can function independently of CD28 [9,13,14] to activate T cells [10,15,16]. 4-1BB can influence cytokine production, proliferation and survival of T cells in vitro and in vivo [8][9][10][16][17][18][19][20][21][22][23][24]. Stimulatory anti-4-1BB antibodies show a preferential role for 4-1BB in CD8 + T cell activation in vitro [20].…”
Section: Introductionmentioning
confidence: 99%
“…4-1BB can influence cytokine production, proliferation and survival of T cells in vitro and in vivo [8][9][10][16][17][18][19][20][21][22][23][24]. Stimulatory anti-4-1BB antibodies show a preferential role for 4-1BB in CD8 + T cell activation in vitro [20]. However, purified CD4 T cells as well as antigen-specific MHC class II-restricted TCR transgenic cells can clearly respond to 4-1BBL in vitro [15,17,22,25].…”
Section: Introductionmentioning
confidence: 99%
“…40 Although stimulation of the 4-1BB:4-1BBL signaling pathway leads to both CD4 þ and CD8 þ T-cell activation, 19,41,42 evidence has shown that it caused the preferential expansion of CD8 þ T cells. Shuford et al 43 used mAbs to show that 4-1BB signaling markedly enhanced interferon-g production from CD8 þ T cells and that the a-4-1BB mediated proliferation of CD8 þ T cells appeared to be IL-2 independent. Use of a-4-1BB Ab, in vitro, to stimulate CD8 þ T cells with downregulated CD28 showed that CD28 expression was restored, while expression of the memory marker CD45RO and CC chemokine receptor 6 (CCR6) and the content of granzyme B were also enhanced.…”
Section: Role Of 4-1bb:4-1bbl In Primary Immune Responsesmentioning
confidence: 99%